Health Education Using Leaflet Media On Female Adolescents' Knowledge About Vaginal Discharge At State Junior High School 2 Semen, Kediri Regency - Putri, Stevani Basuki; Astutik, Reni Yuli; Istighosah, Nining; Ina, Erni Tamu (Journal for Quality in Public Health, 2025)
Lack of reproductive health knowledge about vaginal discharge is caused by limited access to information media and lack of awareness to maintain cleanliness of reproductive organs (personal hygiene) are factors causing vaginal discharge. The purpose of this study was to evaluate the effect of health education using leaflet media on the knowledge of adolescent girls about vaginal discharge.The research design used a pre-experimental one-group pre-post test design. The population was 80 respondents using a simple random sampling technique so that the sample was 67 respondents. The data collection technique used a questionnaire and data analysis used the Wilcoxon test. The results of the study showed that before being given treatment, most respondents (70.1%) had poor knowledge about vaginal discharge and after being given treatment, most respondents (73.1%) had good knowledge about vaginal discharge. The results of data analysis using the Wilcoxon test to analyze obtained a sig value (2-tailed) or p value = 0.000 <0.05 so that H1 was accepted, meaning that there was an effect of health education using leaflet media on the knowledge of adolescent girls about vaginal discharge at State Junior High School 2 Semen, Kediri Regency.An important role in influencing human behavior such as attitudes, actions and knowledge is to provide health education, because health education is a learning mechanism carried out by individuals or groups.